Faktor-Faktor Yang Mempengaruhi Harga Saham Dari Sisi Audit - Adinda Risma Juniarti; Auliffi Ermian Challen; Lenda Komala (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The purpose of this study is to analyze the relationship between audit opinion and public accounting firms with the stock prices of banking businesses traded on the Indonesia Stock Exchange. This research will concentrate on the banking business because audit compliance in this business is emphasized by financial institutions as well as strict supervision and laws in which they operate. Many significant financial institutions have seen their stock prices rise, indicating that more people will be attracted to buying banking sector stocks. If the company's future looks bright, investors will be willing to pay more for the stock. This research relies on secondary data from other sources including annual reports and auditors' reports. For 2016-2021, a total of 47 banking businesses were included as the study population. This study took a sample of 28 banking businesses using a systematic random sampling technique. Logistic regression analysis using SPSS 26.0 was used for analysis. The findings show that an increase in share price is associated with a favorable audit opinion, while the size of a public accounting firm has no impact on stock price.